The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1097/mej.0b013e328302c819
|View full text |Cite
|
Sign up to set email alerts
|

Chiari I malformation with syrinx: an unexpected diagnosis in the emergency department

Abstract: The authors describe a case of syringomyelia associated with Chiari I malformation in a patient in whom acute symptomatic exacerbation occurred after cervical spine trauma. The authors review the various factors in the pathogenesis of this unusual sequence of events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Wan et al [9] described a symptomatic 'conversion' of previously asymptomatic Chiari Type I following minor head and neck trauma. Other authors have described the discovery of symptomatic Chiari Type I following motor vehicle crashes and what is typically described as 'whiplash' trauma [10,11], in which the injury mechanism is a result of inertial loading of the spine and skull [12].…”
Section: Introductionmentioning
confidence: 98%
“…Wan et al [9] described a symptomatic 'conversion' of previously asymptomatic Chiari Type I following minor head and neck trauma. Other authors have described the discovery of symptomatic Chiari Type I following motor vehicle crashes and what is typically described as 'whiplash' trauma [10,11], in which the injury mechanism is a result of inertial loading of the spine and skull [12].…”
Section: Introductionmentioning
confidence: 98%
“…Other authors have reported tonsillar descent and neurological deterioration in patients with asymptomatic CM-I after traumatic brain injury and minor traumas. 6,13,33,46,58,61 Lee et al 31 reported on a patient with acquired CM-I and an associated syrinx secondary to obstructive hydrocephalus caused by a giant craniopharyngioma. The CM-I resolved with resection of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…40,57 The authors of numerous reports have demonstrated, however, that acute neurological deterioration can occur in patients with CM-I and acquired Chiari malformations. 2,3,10,11,13,14,29,31,33,43,[46][47][48][49]58,59,61 Milhorat et al 35 also reported on a case of acute myelopathy secondary to VP shunt malfunction and the onset of acute syringomyelia.…”
mentioning
confidence: 99%